2021
DOI: 10.1007/s12144-021-02537-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term emotional consequences of parental alienation exposure in children of divorced parents: A systematic review

Abstract: Although the emotional consequences of childhood exposure to parental alienation behaviors in children and adolescents of divorced parents are known, there is scarce evidence on their long-term consequences in adulthood. Therefore, this work aims to conduct a systematic review of the state of research in this area and its main conclusions and identify gaps and limitations to guide future research. A search of the literature was performed in electronic databases PsycInfo, MEDLINE, SCOPUS, Web of Science, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In this context, children have the right to education, affection, and protection from both parents. However, divorce can affect the fulfillment of these rights, where a child might lose the opportunity to receive love and guidance from one parent (Miralles et al, 2023). Additionally, children can also be adversely affected by conflicts between parents.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, children have the right to education, affection, and protection from both parents. However, divorce can affect the fulfillment of these rights, where a child might lose the opportunity to receive love and guidance from one parent (Miralles et al, 2023). Additionally, children can also be adversely affected by conflicts between parents.…”
Section: Introductionmentioning
confidence: 99%
“…Parental alienation has repercussions on the child, as it annihilates their capacity to offer and receive affection from one of their parents. The child can develop: low self-esteem, lack of trust in oneself and others, depression, substance abuse, addiction, anxiety, self-sufficiency, uncertain attachment, feelings of loss, feelings of abandonment, feelings of guilt, and incapacity to respect authority, which are related to psychiatrical afflictions [ 9 ]. Also, negative effects were observed in the case of the alienated parent, including suicide attempts [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This puts pressure on the child to take sides in the conflict through the attempt of one parent to form alliances with the child against the other parent [ 40 ]. This phenomenon has been conceptualized in different ways, such as parental interference, in which parents utilize behaviors, strategies, or actions to hinder and damage the relationship of the child with the other parent [ 41 ]. In an extreme parental interference situation, the child might lose contact with and reject the other parent [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies demonstrate that children who are exposed to such negative parental attitudes during the divorce process and the post-divorce period show anger, guilt, hostility, impulse control problems, low self-confidence and self-esteem, anxiety, depression, difficulties in personal and social relationships, and diminished academic performance (for a review, see [ 41 ]). Although there is less evidence regarding the long-term implications of this phenomenon in adult children, a few studies conducted in this developmental period have found negative emotional, psychological, and affective consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation